2016
DOI: 10.1128/aem.03615-15
|View full text |Cite
|
Sign up to set email alerts
|

Marker Exchange Mutagenesis of mxaF , Encoding the Large Subunit of the Mxa Methanol Dehydrogenase, in Methylosinus trichosporium OB3b

Abstract: bMethanotrophs have remarkable redundancy in multiple steps of the central pathway of methane oxidation to carbon dioxide. For example, it has been known for over 30 years that two forms of methane monooxygenase, responsible for oxidizing methane to methanol, exist in methanotrophs, i.e., soluble methane monooxygenase (sMMO) and particulate methane monooxygenase (pMMO), and that expression of these two forms is controlled by the availability of copper. Specifically, sMMO expression occurs in the absence of cop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 41 publications
2
20
0
Order By: Relevance
“…In rapid succession, a number of papers documented that the expression of Mxa-MeDH and Xox-MeDH in a variety of methanotrophs and methylotrophs was strongly dependent on the availability of REEs, primarily light REEs (124)(125)(126)(127)(128). In the absence of REEs, little expression of xox genes was observed, while the expression of mxa genes was high.…”
Section: Function Of Rare-earth Elements In Methanotrophsmentioning
confidence: 99%
“…In rapid succession, a number of papers documented that the expression of Mxa-MeDH and Xox-MeDH in a variety of methanotrophs and methylotrophs was strongly dependent on the availability of REEs, primarily light REEs (124)(125)(126)(127)(128). In the absence of REEs, little expression of xox genes was observed, while the expression of mxa genes was high.…”
Section: Function Of Rare-earth Elements In Methanotrophsmentioning
confidence: 99%
“…We confirmed the physiological modification of the ΔxoxF mutant by growth experiments. Mxa MDH and Xox MDH require calcium and a rare earth element (such as cerium), respectively, for enzymatic activity (15,(27)(28)(29)(30). When Xox MDH is inactive, M. capsulatus (Bath) depends on Mxa MDH for methanol oxidation.…”
Section: Resultsmentioning
confidence: 99%
“…In counterselection for gene disruption in methanotrophs, the sacB gene is employed as the only available marker (8,9,(12)(13)(14)(15)(16). Levansucrase, encoded by the sacB gene, converts sucrose into levan, which accumulates in the periplasmic space, thereby causing cell death in Gram-negative bacteria (17).…”
mentioning
confidence: 99%
“…S3a and b). A previous study reported that the lanthanide dependency of the ΔmxaF mutant of M. trichosporium OB3b became more conspicuous with repeated subcultures, possibly due to the alleviation of the carryover of lanthanides (Farhan Ul Haque et al, 2016). Hence, each culture was further subjected to repeated subcultures.…”
Section: Growth Properties Of Isolated Methanotrophsmentioning
confidence: 99%